The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.nicl.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Disorder-specific characteristics of borderline personality disorder with co-occurring depression and its comparison with major depression: An fMRI study with emotional interference task

Abstract: Borderline personality disorder (BPD) and major depressive disorder (MDD) are both associated with abnormalities in the regulation of emotion, with BPD being highly comorbid with MDD. Disorder-specific dysfunctions in BPD, however, have hardly been addressed, hence the lack of knowledge pertaining to the specificity of emotion processing deficits and their commonality with MDD.24 healthy comparison subjects, 21 patients with MDD, and 13 patients with comorbid BPD and MDD (BPD + MDD group) were studied using fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Previous research showed a characteristic bias of social information processing in BPD (e.g., Chechko et al, 2016 ; Niedtfeld et al, 2016 ) and supported the idea that the biases are related to interpersonal problems in BPD (e.g., Herbort et al, 2016 ; Whalley et al, 2015 ). Examples for the characteristic bias are that patients tend to perceive ambiguous facial expressions in a negative way (see Domes et al, 2009 for a review) and quickly feel rejected (e.g., Arntz et al, 2011 ; Staebler et al, 2011a ).…”
Section: Introductionsupporting
confidence: 54%
“…Previous research showed a characteristic bias of social information processing in BPD (e.g., Chechko et al, 2016 ; Niedtfeld et al, 2016 ) and supported the idea that the biases are related to interpersonal problems in BPD (e.g., Herbort et al, 2016 ; Whalley et al, 2015 ). Examples for the characteristic bias are that patients tend to perceive ambiguous facial expressions in a negative way (see Domes et al, 2009 for a review) and quickly feel rejected (e.g., Arntz et al, 2011 ; Staebler et al, 2011a ).…”
Section: Introductionsupporting
confidence: 54%
“…Using a conjunction analysis, we sought to determine the neuronal circuitries involved in multimodal integration irrespective of the type of sensory stimuli, and identified a network of brain areas spanning the prefrontal, the parietal, and the visual cortices. Thus, during MSI irrespective of the sensory stimuli (but always including visual information), we observed a conjoint recruitment of the brain network related to visual processing (the striate and extrastriate cortices), spatial perception and sustained attention (the parietal cortex) (e.g., Malhotra, Coulthard, & Husain, ), inhibition and multisensory attention (the insula) (e.g., Ghahremani, Rastogi, & Lam, ), vigilance, error response monitoring and resolution of response conflict (the medial prefrontal cortex) (Chechko et al, ; e.g., Chechko et al, ; Chechko et al, ), and, finally, motor output (the precentral gyrus). This corroborates the findings of studies that focused on the integration of auditory stimuli with other sensory modalities and favored the role of those areas in MSI processes, often referring to the IPS as one of the central hubs (Bremmer et al, ; Calvert & Thesen, ; Grefkes & Fink, ).…”
Section: Discussionmentioning
confidence: 80%
“…naming colors) (Williams, Mathews, & MacLeod, 1996).The emotional analogue of the Stroop task is often utilized to study psychiatric disorders (e.g. Chechko et al, 2012Chechko et al, , 2013Chechko et al, , 2016 by provoking interference through the semantic incompatibility between an emotional target (emotional face) and an emotional distractor (emotionally salient word), as the individual's current (mental) condition is reflected in a disproportionate reaction for negative (relevant to the own condition) compared to positive (irrelevant to the own condition) emotional stimuli (Williams et al, 1996). Here, the less familiar task is the recognition of the facial expression, which has to be enhanced by suppressing the habitual response like reading.…”
Section: S Stickel Cumulative Cortisol Secretion In Pregnancy 23 Emmentioning
confidence: 99%